Recent Advances in Natural Language Processing III : Selected Papers from RANLP 2003 - Nicolov, Nicolas (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2004)
This volume brings together revised versions of a selection of papers presented at the 2003 International Conference on "Recent Advances in Natural Language Processing". A wide range of topics is covered in the volume: semantics, dialogue, summarization, anaphora resolution, shallow parsing, morphology, part-of-speech tagging, named entity, question answering, word sense disambiguation, information extraction. Various 'state-of-the-art' techniques are explored: finite state processing, machine learning (support vector machines, maximum entropy, decision trees, memory-based learning, inductive